Prevalence of iron deficiency anaemia in chronic kidney disease patients not on renal replacement therapy: a cross-sectional observational study - Parate, Tilottama R.; Ghadge, Varada A.; Parate, Ramesh U. (International Journal of Research in Medical Sciences, 2025)
Background: Chronic kidney disease (CKD) is a leading cause of mortality in India. Iron deficiency anaemia (IDA), both absolute and functional, is prevalent among CKD patients, especially in developing countries. Timely diagnosis and treatment are essential to reduce associated morbidity and mortality. Methods: A cross-sectional observational study was conducted from August 2022 to July 2024 at Indira Gandhi Government Medical College, Nagpur. The study included 100 diagnosed CKD patients (stages 3–5) not on renal replacement therapy, fulfilling specific inclusion and exclusion criteria. Results: Among the participants, 35% were in stage 4 and 38% in stage 5 CKD. The majority (37%) were aged 51–60 years. A significant association was observed between mean haemoglobin levels and CKD stages in males. All females were anaemic, indicating a significant link between gender and anaemia status. Regarding red blood cell morphology, 51% exhibited a normocytic normochromic pattern, while 29% had a microcytic hypochromic pattern. A statistically significant correlation was found between serum iron profile and CKD stages. Of the 91 anaemic patients, 31 (34.06%) had IDA. Conclusions: CKD predominantly affects older adults, with the highest prevalence in the 51–60 age group and a male predominance. Serum iron profiles deteriorate as CKD stages advance, correlating with increased prevalence and severity of IDA.